Pemanfaatan Dana Desa Sebagai Upaya Peningkatan Kesejahteraan Masyarakat Desa dari Perspektif Keuangan Daerah - Subhan Purwadinata; Ahmad Zaenal Wafik; Iwan Harsono (EKOMA : Jurnal Ekonomi, Manajemen, Akuntansi, 2024)
This research investigates the role of Village Fund utilization in enhancing the welfare of rural communities from the perspective of local finance. Through a qualitative approach and data collection from relevant informants, the study found that effective Village Fund utilization requires transparency, accountability, and active community participation. The results indicate that Village Fund utilization has significant potential to contribute significantly to the improvement of rural community welfare, provided that management is optimal and supported by appropriate policies.